Community‐acquired Chryseobacterium indologenes in an immunocompetent patient. Issue 1 (March 2014) - Cunha, Vitória; Ferreira, Melanie; Fonseca, Ana Glória; Diogo, José
Abstract : Introduction: Chryseobacterium indologenes is a rare pathogen in the human microflora. Nearly half of the published cases refer to nosocomial infections, and the vast majority of patients had underlying immunocompromising conditions. The clinical evolution is usually conducive to antibiotic treatment, but despite being low‐virulent bacteria, infections have often been associated with a high mortality rate as a result of the increased resistance to antibiotics, and the absence of a gold standard for management. Case presentation: A 60‐year‐old male immunocompetent patient was admitted for acute onset of fever, abdominal pain and dysuria. Blood and urine cultures were positive for multiresistant C. indologenes, susceptible only to ciprofloxacin. Clinical improvement was observed on ciprofloxacin antibiotic therapy. Conclusion: This is, to the best of our knowledge, the first Portuguese report of community‐acquired C. indologenes bacteraemia in an immunocompetent patient, a rare disease agent with low pathogenicity but capable of causing severe illness.